2016
DOI: 10.1523/jneurosci.3392-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Charitable Brain: Empathy, Perspective Taking, and Attention Shifts Differentially Predict Altruistic Giving

Abstract: Altruistic behavior varies considerably across people and decision contexts. The relevant computational and motivational mechanisms that underlie its heterogeneity, however, are poorly understood. Using a charitable giving task together with multivariate decoding techniques, we identified three distinct psychological mechanisms underlying altruistic decision-making (empathy, perspective taking, and attentional reorienting) and linked them to dissociable neural computations. Neural responses in the anterior ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
218
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(261 citation statements)
references
References 85 publications
19
218
1
Order By: Relevance
“…We suggest, first, that affect is a critical component of empathy for pain (Tusche et al, 2016): Because experience sharing involves vicarious resonance with the affective states of others, it will be difficult to distinguish empathy priming from affective priming in practice. We stipulate that people unintentionally share the experience of the prime stimuli, and the resulting experience influences target judgment; if the prime depicts pain, then this is likely to involve vicarious negative affect, because pain tends to be experienced as negative.…”
Section: Experiments 3: the Effect Is Not Reducible To Affective Or Sementioning
confidence: 99%
“…We suggest, first, that affect is a critical component of empathy for pain (Tusche et al, 2016): Because experience sharing involves vicarious resonance with the affective states of others, it will be difficult to distinguish empathy priming from affective priming in practice. We stipulate that people unintentionally share the experience of the prime stimuli, and the resulting experience influences target judgment; if the prime depicts pain, then this is likely to involve vicarious negative affect, because pain tends to be experienced as negative.…”
Section: Experiments 3: the Effect Is Not Reducible To Affective Or Sementioning
confidence: 99%
“…"if empathy can be evoked for the victims of injustice, then these two motives can be made to work together rather than at odds" (Batson et al, 1995, p. 1053). Indeed, many prominent perspectives suggest that empathy grounds moral behavior (Decety et al, 2016;de Waal & Preston, 2017;Tusche et al, 2016). Empathy can facilitate moral goals by helping people understand which actions are morally appropriate, particularly in the Ends of empathy 47 ambiguous situations that characterize everyday life (Masto, 2015).…”
Section: Does Empathy Erode Ethics?mentioning
confidence: 99%
“…For instance, prominent lines of research often assumed rather deliberative models (e.g., Latané & Darley, 1970), involving several cognitive steps until an individual decides to provide help in certain situations to anonymous others. Other research suggested empathic concern, perspective taking or elevation as drivers of prosocial behavior (e.g., Batson, 1981;Tusche et al, 2016;Haidt, 2003;see also Michael & Székely, 2017). And even other research highlighted group norms and explained helping by Contagion of Prosocial Behavior 31 the motivation to avoid punishment (Fehr & Gächter, 2002;Silk & House, 2016;Schwartz & Howard, 1981; see also Nook et al, 2016).…”
Section: From Present To Future Researchmentioning
confidence: 98%
“…Furthermore, everyday helping is less influenced by the helper's empathic concern regarding the person in need for help, which is crucial for altruism (Batson et al 1981(Batson et al , 2007Tusche et al, 2016;Leiberg, Klimecki & Singer, 2011) and which increases with the severity of the situation (Darley & Batson, 1973; see also Warneken & Tomasello, 2009;Tomasello, 2014;Tomasello, 2016;Murphy, Ackermann & Handgraaf, 2011). Altruism could also result into prosocial behavior that involves sacrificially large costs for the helper, which is not the case for everyday helping.…”
Section: Contagion Of Prosocial Behaviormentioning
confidence: 99%